2016
DOI: 10.4172/2167-0277.1000243
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ramadan Observance on Sleep Pattern and Wakefulness at Work among Medical Trainer in Tunisia

Abstract: Introduction: Muslims practice intermittent Islamic fasting all over the globe each year during Ramadan. This practice induces several changes that may affect work performance. The aim of this study is to evaluate the impact of fast during Ramadan on eating behaviors, sleep habits, daytime sleepiness, and professional life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…More recently, Mertens and collaborators [5] in Belgium found that, in a sample of 20 fasting workers, daytime sleepiness moderately increased, whereas neuro-performance remained unaffected and concentration improved with large inter-individual differences. Other studies have investigated this topic in Arabic countries, reporting similar findings [6,8,25,31,32].…”
Section: Discussionsupporting
confidence: 63%
“…More recently, Mertens and collaborators [5] in Belgium found that, in a sample of 20 fasting workers, daytime sleepiness moderately increased, whereas neuro-performance remained unaffected and concentration improved with large inter-individual differences. Other studies have investigated this topic in Arabic countries, reporting similar findings [6,8,25,31,32].…”
Section: Discussionsupporting
confidence: 63%
“…Msaad et al observed delayed average bedtimes during Ramadan, leading to daytime drowsiness and reduced productivity, indicating sleep pattern disruptions. 4 Overall, we recommend a wider study of the determinants of sleep health that could contribute to poor sleep quality and insomnia, across various contexts. This could help with the development of targeted and effective strategies for different subsets of adults from Tunisia, to address the specific underlying causes of sleep disturbances.…”
Section: Dear Editormentioning
confidence: 99%